Great physicists the life and times of leading physicists from Galileo to Hawking - Cropper William H (Oxford OUP, 2001)
This book provides encapsulated histories of 30 physicists who have made major contributions to the development of physics over the last five centuries, from Galileo to Hawking. ... This has the wonderful effect of laying out the development of physics i
Keywords: Biographies; Physicists